Cost-Utility Analysis: Sartorius Flap versus Negative Pressure Therapy for Infected Vascular Groin Graft Managment. Issue 11 (November 2015) - Chatterjee, Abhishek; Macarios, David; Griffin, Leah; Kosowski, Tomasz; Pyfer, Bryan J.; Offodile, Anaeze C.; Driscoll, Daniel; Maddali, Sirish; Attwood, John
Abstract : Background: Sartorius flap coverage and adjunctive negative pressure wound therapy (NPWT) have been described in managing infected vascular groin grafts with varying cost and clinical success. We performed a cost–utility analysis comparing sartorius flap with NPWT in managing an infected vascular groin graft. Methods: A literature review compiling outcomes for sartorius flap and NPWT interventions was conducted from peer-reviewed journals in MEDLINE (PubMed) and EMBASE. Utility scores were derived from expert opinion and used to estimate quality-adjusted life years (QALYs). Medicare current procedure terminology and diagnosis-related groups codes were used to assess the costs for successful graft salvage with the associated complications. Incremental cost-effectiveness was assessed at $50, 000/QALY, and both univariate and probabilistic sensitivity analyses were conducted to assess robustness of the conclusions. Results: Thirty-two studies were used pooling 384 patients (234 sartorius flaps and 150 NPWT). NPWT had better clinical outcomes (86.7% success rate, 0.9% minor complication rate, and 13.3% major complication rate) than sartorius flap (81.6% success rate, 8.0% minor complication rate, and 18.4% major complication rate). NPWT was less costly ($12, 366 versus $23, 516) and slightly more effective (12.06 QALY versus 12.05 QALY) compared with sartorius flap. Sensitivity analyses confirmed the robustness of the base case findings; NPWT was either cost-effective at $50, 000/QALY or dominated sartorius flap in 81.6% of all probabilistic sensitivity analyses. Conclusion: In our cost–utility analysis, use of adjunctive NPWT, along with debridement and antibiotic treatment, for managing infected vascular groin graft wounds was found to be a more cost-effective option when compared with sartorius flaps.